Effectiveness of life skills intervention on depression, anxiety and stress among children and adolescents: a systematic review - Sherif, Yosra; Azman, Ahmad Zaid Fattah; Awang, Hamidin; Mokhtar, Siti Aisha; Mohammadzadeh, Marjan; Alimuddin, Aisha Siddiqah (Universiti Sains Malaysia Press, 2023)
Children and adolescents are at a significantly high risk of mental health problems during their lifetime, among which are depression and anxiety, which are the most common. Life skills education is one of the intervention programmes designed to improve mental wellbeing and strengthen their ability to cope with the daily stresses of life. This review aimed to identify and evaluate the effect of life skills intervention on the reduction of depression, anxiety and stress among children and adolescents. Following the Population, Intervention, Comparison and Outcome (PICO) model and the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2009 checklist, eight databases (Academic Search Complete, CINAHL, Cochrane, MEDLINE, Psychology and Behavioural Sciences Collection, PubMed, Scopus and Web of Science) were systematically reviewed from 2012 to 2020. The search was limited to English papers only. It included published experimental and quasi-experimental studies addressing the effect of life skills interventions on the reduction of at least one of the following mental health disorders: depression, anxiety and stress among children and adolescents (from the age of 5 years old to 18 years old). We used the Joanna Briggs Institute checklist for experimental and quasi-experimental studies to evaluate the quality of the included studies. This study was registered in PROSPERO CRD42021256603. The search identified only 10 studies (three experimental and seven quasi-experimental) from 2,160 articles. The number of the participants was 6,714 aged between 10 years old and 19 years old. Three studies in this review focused on depression and anxiety, whereas one study investigated depression and the other anxiety. Three studies targeted only stress and two examined the three outcomes, namely, depression, anxiety and stress. Almost in all studies, the life skills intervention positively impacted mental disorders, considering the differences among males and females. The overall methodological quality of the findings was deemed to be moderate to high. Our results clearly indicated the advantages of life skills programmes among adolescents in different settings and contexts. Nonetheless, the results highlight some important policy implications by emphasising the crucial roles of developers and policymakers in the implementation of appropriate modules and activities. Further research examining life skills intervention with a cultural, gender perspective, age-appropriate and longterm effect is recommended.